The customs union issue - Viner, Jacob (New York : Carnegie Endowment for International Peace, 1950)
This stud examines the nature, purposes, and mode of operation of the customs union as one special form of tariff unification
Bibliography: p. 171-211.
osc 24/08/2018
Loans
Keywords: Customs unions